Making and remaking mosques in Senegal - Cantone, Cleo. (Islam in Africa, 2012)
This book constitutes a seminal contribution to the fields of Islamic architectural history and gender studies. It is the first major empirical study of the history and current state of mosque building in Senegal and the first study of mosque space from a gender perspective. The author positions Senegalese mosques within the field of Islamic architectural history, unraveling their history through pre-colonial travelers' accounts to conversations with present-day planners, imams and women who continually shape and reshape the mosques they worship inches Using contemporary Dakar as a case study, the book's second aim is to explore the role of women in the "making and remaking" of mosques. In particular, the rise of non-tariqa grass-roots movements (i.e.: the "Sunni/Ibadou" movement) has empowered women (particularly young women) and has greatly strengthened their capacity to use mosques as places of spirituality, education and socialization. The text is aimed at several specialized readerships: readers interested in Islam in West Africa, in the role of women in Islam, as well as those interested in the sociology and art-history of mosques.